PENGARUH KONSEP DIRI DAN KONTROL ORANG TUA TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN EKONOMI DI SMA N 01 SIPORA SELATAN - Yoga Witadia; Dessyta Gumanti; Widya Astuti (Ekasakti Educational Scientific Journal, 2025)
This study aims to analyze 1) the influence of self-concept on the learning outcomes of class XI students of SMA 01 Sipora Selatan. 2) the influence of parental control on the learning outcomes of class XI students of SMA Sipora Selatan. 3) the influence of self-concept and parental control on the learning outcomes of class XI students of SMA N 01 Sipora Selatan. This type of research is quantitative research using descriptive associative. The population in the study were all class XI students of SMA N 01 Sipora Selatan. Sampling using saturated sampling techniques. So the sample amounted to 60 people. The instruments used for the study were questionnaires and documentation using Multiple Linear Regression tests and hypothesis testing with t-tests and F-tests. The results of the study showed that: 1) There is a positive and significant influence between self-concept (X1) on the learning outcomes of class XI students of SMA N 01 Sipora Selaran. It is known that the regression coefficient value β of emotional intelligence is positive at 0.138 and the t count value is 2.455> t table of 1.67203 with a significant value of 0.017> α = 0.05. 2) There is a positive and significant influence between parental control (X2) on the learning outcomes of class XI students of SMA N 01 Sipora Selatan. It is known that the regression coefficient value β of parental control is positive at 0.111 and the t count value is 2.463> t table of 1.67203 with a significant value of 0.017 <α = 0.05. 3) There is an influence of self-concept (X1), and parental control (X2) simultaneously on learning outcomes (Y). It is known that the significance value for the influence of X1 and X2 simultaneously on Y is 0.009 <0.05 and the F count value is 5.162> F table 3.16. This shows that there is an influence of self-concept and parental control simultaneously on learning outcomes (Y) in class XI students of SMA N 01 Sipora Selatan.